How fast are the tourism countries growing? The international evidence, 1980-95 - Francesco Pigliaru; Alessandro Lanza (European Regional Science Association (ERSA), 2003)
International data on per-capita income show that, in the last few years, growth in some countries specialized in tourism was faster than in the average country included in the World Bank-World Development Indicators. Fast growth in tourism countries might be due to fast, unsustainable exploitation of a given endowment of natural resources, or to a more robust and sustainable phenomenon (due for instance to the existence of a favourable trend in the terms of trade between tourism and other activities). To date, little analytical or empirical studies are available to explain such a performance and the underlying mechanisms. This is unfortunate. For instance, a better understanding of the above issues is crucial to assess the role tourism can play in less developed countries and regions. The main objective of our paper is to fill this gap in the current literature. We address the following questions: (i) What are the economic mechanisms capable to generate fast growth in tourism countries' (ii) How empirically robust is the positive relationship between faster growth and tourism specialization? (iii) Is the growth path associated to tourism specialization sustainable? We use a two-sector endogenous growth model to address question (i). In particular, we define the conditions required for small countries to specialise in tourism and to enter the faster growth path. Our suggestion is that what matters is, first, a country's relative endowment of the natural resource, and, second, a low elasticity of substitution between tourism services and other consumption goods, so that the terms of trade move fast enough in favour of the tourism countries. Question (ii) is addressed by means of standard cross-section and panel growth regressions aimed at testing whether specialisation in tourism is robustly associated with faster than average per capita growth in international dataset over the last twenty years. Preliminary results indicate that such relationship might be robust indeed for the sample period. Question (iii) will be dealt with using the same international dataset. First, by examining their comparative performance in several sub-periods, we will assess whether tourism countries are characterized by a more pronounced than average slow-down in growth. Second, we will try to assess to what extent growth in tourism countries is due to a favourable terms-of-trade effect rather than fast expansion of the industry (which imply faster exploitation of the natural resource).
Keywords: 330